Impact of Game-Based Discovery Learning on Elementary Students' Engagement and Learning Motivation in Social Studies - Andari, Yenny Dwi; Waris, Waris; Adhim, Fauzan (Journal La Edusci, 2025)
The study was conducted to analyze the effect of discovery learning using the Ludo King educational game on student learning activeness and motivation in Social Studies. The study involved the fifth-grade students of Pasirian 06 State Elementary School, with a total of 27 students. This research is categorized as quasi-experimental with a one-group pretest-posttest design, and hypothesis testing was performed using the Mann-Whitney U test. The results indicated a significance value of 0.000 < 0.05 for student learning activeness and motivation. Therefore, it can be concluded that the application of the discovery learning model using the Ludo King game has a significant effect on increasing student activeness and motivation in fifth-grade Social Studies at Pasirian 06 State Elementary School